THE EFFECT OF REACTION PARAMETERS ON THE YIELD OF POLYOL FROM RUBBER SEED OIL - Mudjijono, Mudjijono; Utami, Sasanti (Alchemy Jurnal Penelitian Kimia, 2013)
The research on the effect of reaction parameters on the yield of polyol from rubber seed oil and palm oil as a comparison compound has been carried out. Polyol was synthesized by the reaction of oils and peracid. Peracid was produced by mixing of formic acid (HCOOH) and hydrogen peroxide (H2O2) with catalyst (H2SO4). Polyol was synthesized successfully based on spectra analysis of fourier transform infrared spectroscopy (FTIR) with FTIR spectra of PEG-400 and polyol of Suryani (2009). The results of t-test analysis showed that there was no difference of the polyols yield from rubber seed oil and palm oil. Analysis of a simple graph showed that the optimum yield of polyols were obtained in the same conditions, which are molar ratio of HCOOH:H2O2 4:1 mol/mol and H2SO4concentration 4% v/v oil. Physical characterization included density and viscosity of polyols, showed that within the limits of measurement error, density of polyols were same, whereas viscosity of polyols showed the differences.